Adolescents Have Twice the Revision Rate of Young Adults After ACL Reconstruction With Hamstring Tendon Autograft: A Study From the Swedish National Knee Ligament Registry. Issue 10 (11th October 2021) - Thorolfsson, Baldur; Svantesson, Eleonor; Snaebjornsson, Thorkell; Sansone, Mikael; Karlsson, Jon; Samuelsson, Kristian; Senorski, Eric Hamrin
Background: Previous studies have identified young age as a risk factor for anterior cruciate ligament (ACL) revision. However, few studies have looked separately at pediatric patients and adolescents with regard to outcomes after ACL reconstruction. Purpose: To determine whether patient age at ACL reconstruction affects the risk of undergoing revision surgery in young patients. Study Design: Cohort study; Level of evidence, 3. Methods: This study was based on data from the Swedish National Knee Ligament Registry. Patients aged 5 to 35 years who underwent a primary ACL reconstruction with a hamstring tendon autograft between January 1, 2005, and December 31, 2015, were included. The cohort was stratified into different age groups of pediatric patients, adolescents, and young adults to estimate patients with open, recently closed, and closed epiphyses, respectively. The primary endpoint was ACL revision. A multivariable Cox regression model was used to assess the ACL revision rate. The results were expressed as hazard ratios (HRs) and 95% CIs. Results: A total of 36, 274 ACL reconstructions were registered during the study period. Of these, 2848 patients were included in the study: 47 pediatric patients (mean age, 13.6 years; range, 9-15 years), 522 adolescents (mean age, 17.4; range, 14-19 years), and 2279 young adults (mean age, 27.0; range, 20-35 years). A total of 31 patients (1.1%) underwent ACL revision within 2 years (0 pediatric patients, 9 adolescents [1.7%], and 22 young adults [1.0%]) and a total of 53 patients (2.6%) underwent ACL revision within 5 years (2 pediatric patients [6.9%], 15 adolescents [3.9%], and 36 young adults [2.2%]). The adolescent age group had a 1.91 times higher rate of ACL revision compared with the young adults (HR = 1.91 [95% CI, 1.13-3.21]; P = .015). There were no differences in revision rates between the pediatric age group and the young adults (HR = 2.93 [95% CI, 0.88-9.79]; P = .081). Conclusion: Adolescents had almost twice the rate of revision ACL reconstruction compared with young adults.